(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The definition of investment in international investment law is of fundamental importance to the question of whether a tribunal has jurisdiction over the subject matter of the dispute. This note examines the meaning of investment under international treaties and the ICSID Convention and discusses specific issues that can arise in relation to the definition of investment.